Pruebas de laboratorio en el diagnóstico de infecciones bacterianas en adolescentes embarazadas. - Freire Aldas, María Fernanda (2024)
Teenage pregnancy has significant repercussions on the lives of young women, causing effects on their psychosocial growth and physical well-being, especially those between 10 and 19 years old, who face a greater risk of developing systemic infections. The present work is based on reviewing medical records of pregnant adolescent patients who attended the General Teaching Hospital of Riobamba, 2021 - 2023. The objective was to specify the laboratory tests for the diagnosis of bacterial infections at the vaginal level. The tests performed: blood count, blood chemistry, urine culture, and vaginal secretion culture. This descriptive study had a non-experimental, crosssectional, and retrospective field design. The study population was 153 patients, and the inclusion and exclusion criteria were applied, obtaining a sample of n=108. The results showed a statistically significant relationship (p<0.05) of factors associated with infections, gestational age (p= 0.034), complications of newborn (p= 0.024), factors that are not associated such as menarche (p=0.726), type of delivery (p= 0.070) and place of residence (p=0.870), urine culture and culture of vaginal secretion were specific tests, with 58% of pregnant adolescents who did not present infection, 15% Escherichia coli, 13% mixed vaginitis, Candida albicans 7%, and finally 6% for Gardnerella vaginalis, a higher prevalence of bacterial infections due to Escherichia coli and Gardnerella vaginalis was observed giving a total of 21%. Therefore, laboratory tests help diagnose bacterial infections as a potential risk factor for obstetric complications